NATIONALISM AND ÉCRITURE - Karatani, Kojin (Surfaces)

(untitled) (Les Presses de l’Université de Montréal, 1995)
In referring to Jacques Derrida's critique of Western phonocentrism, this paper argues that phonocentrism is not simply a Western phenomenon but is linked to the emergence of the modern nation-state. In this context, this paper examines the question of nationalism and écriture in Japan, discussing the historical confrontation between Chinese characters (kanji) and phonetic signs (kana), the work of the contemporary Japanese linguist Motoki Tokieda, among other issues.